Structural steel design to Eurocode 3 and AISC specifications - Bernuzzi, Claudio; Cordova, Benedetto (John Wiley Blackwell, 2016)
Structural Steel Design to European and United States Specifications deals with the theory and practical applications of structural steel design. Structural Steel Design to Eurocode 3 and AISC Specifications deals with the theory and practical applications of structural steel design in Europe and the USA. The book covers appropriate theoretical and background information, followed by a more design-oriented coverage focusing on European and United States specifications and practices, allowing the reader to directly compare the approaches and results of both codes. Chapters follow a general plan, covering:?<U+0009>A general section covering the relevant topics for the chapter, based on classical theory and recent research developments?<U+0009>A detailed section covering design and detailing to Eurocode 3 specification?<U+0009>A detailed section covering design and detailing to AISC specificationsFully worked examples are using both codes are presented. With construction companies working in increasingly international environments, engineers are more and more likely to encounter both codes. Written for design engineers and students of civil and structural engineering, this book will help both groups to become conversant with both code systems.
Keywords: Steel, Structural -- Standards.; Building, Iron and steel -- Standards.; elektronické knihy; electronic books